DERADICALIZATION AND ANTI-TERRORISM FOR EXNAPITER CHILDREN: Case Study of Al-Hidayah Boarding School - Widodo, Wahyu Marrend; Ritonga, Sakti (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2023)
This research study is about the educational model developed related to prevention strategies of extremist children to prevent them from following the steps or experiences of their parents as perpetrators of terrorist acts. One of the places of analysis in this study is the al hidayah Islamic boarding school. This research was conducted with one approach, namely a qualitative approach, with this approach obtained sources of information through observation, interviews and documentation needed for this research by the management of the school. Then, the study used phenomenological methods. The method is able to describe how an individual feels the experience and provide a picture of the phenomenon. It is therefore interesting to conduct research on how terrorist prevention and countermeasures education models developed and designed by ex-terrorist convicts against children of ex-terrorists or non-terrorists. Study findings show that the establishment of Islamic boarding schools is motivated by self-awareness that utilizing oneself for others by promoting Islamic values that are peaceful and non-violent, these values are the basis for developing an educational model in al hidayah Islamic boarding schools